Kinetics of Struvite Crystals Formation through Adsorption and Crystallization Using Zeolite Modification - Eko Ariyanto; Dian Kharismadewi; Mardwita Mardwita; Stefanus Muryanto (Iraqi Journal of Science, 2024)
This study observed the formation of struvite crystals in wastewater using natural zeolite activated with Mg2+ ions. Mg2+ ions released from natural zeolite would react with PO43- and NH4+ ions from in wastewater to form struvite crystals. The results showed that at pH 8.5, the removal of PO43- and NH4+ ions was more effective using the modified zeolite than the natural zeolite. Adding 40 g/L Zeo-Mg (1) produced the best results, with PO43- (93.32%) and NH4 (40%) adsorption. Meanwhile, 40g/L Zeo-Mg (2) adsorbed 81% PO43- ions and 27.12% NH4+ ions. The eqilibrium time of all the treatments was 40 min. The results of observation through SEM, EDX, and FTIR showed that struvite crystals were formed on the zeolite surface. Kinetic models indicated that the mechanism of struvite formation on the surface of natural and modified zeolite was mainly chemisorption. Further calculations showed that the adsorption of PO43- and NH4+ ion followed the pseudo-first-order kinetic model.